Paradigm shifts in energy: examining the impact of ideas on the implementation of low-carbon policies in the EU and the US - Kelly, Katrina M. (2017)
Climate change and the continuing changes that accompany it require society and its broader institutions to evolve continuously. Today’s continual atmospheric damage requires a commitment to ecological considerations that show consistent and meaningful carbon reductions. The success of global carbon mitigation depends entirely on the capabilities of individual governing bodies agreeing and delivering upon their climate ambitions. However, delivering impactful progress on emissions is a considerable challenge. Although there has been significant research as to what climate mitigation goals should encompass, the policy path and resulting incremental changes needed to achieve them require additional scholarly attention.